ANALISA PENEGAKAN HUKUM YANG BERKEADILAN DALAM KASUS GREGORIUS RONALD TANNUR: KAJIAN TERHADAP PENYIMPANGAN PUTUSAN HAKIM DAN REFORMASI YUDISIAL - MAHARANI SYAHRUL FATH; MRR RATNA ENDANG WIDUATIE; EKARINA MEITA YAHYA; ANGGA FEBRINIANTO; PRIMA ZAIDHAN FIRAS (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
This article examines law enforcement in the case of Gregorius Ronald Tannur, a defendant in a case of violence against Dini Sera Afrianti that resulted in her death. The main focus is the discrepancy between the acquittal issued by the Surabaya District Court and the legal facts, as well as the annulment of the verdict by the Supreme Court after the revelation of a bribery scandal within the judiciary. This case shows a gap in the judicial system, where the integrity of judges can be influenced by external factors. Fair law enforcement requires increased integrity of judges, transparency in decision-making, and more effective oversight mechanisms.